2019
DOI: 10.48550/arxiv.1911.10716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Principles Calculations of Superconducting Critical Temperature of ThCr$_2$Si$_2$-Type Structure

Abstract: High critical temperature (T c ) superconductor has a great potential in many industrial applications. However, discovering a compound having high T c is still remaining a big challenge for experimental approach due to time-consuming and high cost. In this paper, we investigated the critical temperature (T c ) of several compounds of ThCr 2 Si 2 -type structure (space group I4/mmm) since some of them had already been investigated and trusted as the potential candidates for superconductivity. First principle ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…AC-susceptibility measurements were conducted using either a Quantum Design Magnetic Properties Measurement (MPMS) System (H DC = 10 Oe, H AC = 1 − 3 Oe, 900 Hz) or a Quantum Design Physical Properties Measurement System (H DC = 10 Oe, H AC = 3 Oe, 1 kHz), measuring T ≥ 2 K. Since prior density function theory (DFT) calculations 52 suggested that CaAg 2 Ge 2 would superconduct near T = 1.5 K, we used the 3 He option with the MPMS to measure from 0.4 K to 1.7 K for that sample in addition to our standard measurement above 2 K.…”
Section: Methodsmentioning
confidence: 99%
“…AC-susceptibility measurements were conducted using either a Quantum Design Magnetic Properties Measurement (MPMS) System (H DC = 10 Oe, H AC = 1 − 3 Oe, 900 Hz) or a Quantum Design Physical Properties Measurement System (H DC = 10 Oe, H AC = 3 Oe, 1 kHz), measuring T ≥ 2 K. Since prior density function theory (DFT) calculations 52 suggested that CaAg 2 Ge 2 would superconduct near T = 1.5 K, we used the 3 He option with the MPMS to measure from 0.4 K to 1.7 K for that sample in addition to our standard measurement above 2 K.…”
Section: Methodsmentioning
confidence: 99%
“…Even the closer states allowed for simple electron mobility, which over time affected the materials’ conductivity. Moreover, the compounds adopted the tetragonal ThCr 2 Si 2 -type structure with three-dimensional electron and hole-like multiband Fermi surfaces (FSs), as appeared in the majority of the same types [ 46 , 47 ] and other types [ 41 , 48 , 49 ] of compounds that were related to the phonon-mediated types that were currently under electron-phonon mediated superconductivity, according to a few other research studies that calculated Fermi surfaces (FSs). Due to the crossing and overlapping of bands across the Fermi level of energy, as well as the absence of a gap in both spin states when utilizing two separate (PBE–GGA and GGA + U) approximations, the thorium compound ThMn 2 X 2 band structures generally described the full metallic nature.…”
Section: Resultsmentioning
confidence: 99%